Zwitterionic polymer functionalization of polysulfone membrane with improved antifouling property and blood compatibility by combination of ATRP and click chemistry. (August 2016) - Xiang, Tao; Lu, Ting; Xie, Yi; Zhao, Wei-Feng; Sun, Shu-Dong; Zhao, Chang-Sheng
Graphical abstract: Highlights: ATRP and click chemistry were combined to modify membrane surfaces. Zwitterionic polymer and negatively charged polymers were grafted. The chemical compositions and unique topological structure were controlled. The PSBMA/PNaMAA membrane showed a synergistic effect in the process of coagulation. Abstract: The chemical compositions are very important for designing blood-contacting membranes with good antifouling property and blood compatibility. In this study, we propose a method combining ATRP and click chemistry to introduce zwitterionic polymer of poly(sulfobetaine methacrylate) (PSBMA), negatively charged polymers of poly(sodium methacrylate) (PNaMAA) and/or poly(sodium p-styrene sulfonate) (PNaSS), to improve the antifouling property and blood compatibility of polysulfone (PSf) membranes. Attenuated total reflectance-Fourier transform infrared spectra, X-ray photoelectron spectroscopy and water contact angle results confirmed the successful grafting of the functional polymers. The antifouling property and blood compatibility of the modified membranes were systematically investigated. The zwitterionic polymer (PSBMA) grafted membranes showed good resistance to protein adsorption and bacterial adhesion; the negatively charged polymer (PNaSS or PNaMAA) grafted membranes showed improved blood compatibility, especially the anticoagulant property. Moreover, the PSBMA/PNaMAA modified membrane showed both antifouling property and anticoagulant property, and exhibited a synergistic effect in inhibiting blood coagulation. The functionalization of membrane surfaces by a combination of ATRP and click chemistry is demonstrated as an effective route to improve the antifouling property and blood compatibility of membranes in blood-contact.